Peran Ibu Sebagai Primary Emotional Regulator Dalam Membangun Resiliensi Keluarga: Psikoedukasi Kesiapsiagaan Bencana Berbasis Kampung Siaga Bencana di Desa Siberut Selatan, Kepulauan Mentawai - Mardianto; Devi Lusiria; Frischa Meivilona Yendi; Syafiyah, Aufizzahra; Ira Damayanti; Rahmi Padilla; Ulviatul Humairah (PUSAKO : Jurnal Pengabdian Psikologi, 2025)
The Mentawai Islands are a region with high vulnerability to earthquakes and tsunamis due to their location in the megathrust zone. This condition requires family preparedness as the first unit in disaster response. Mothers play an important role as primary emotional regulators as well as coordinators of family preparedness, making capacity building for mothers a strategic step in fostering community resilience. This community service activity aimed to improve the knowledge, skills, and preparedness of PKK (Family Welfare Movement) members in Muara Siberut Village, South Siberut District, in facing potential disasters. The method used was a participatory psychoeducation program conducted on July 10–12, 2025, involving 26 participants. Evaluation was carried out through pretest–posttest comparisons and the Wilcoxon Signed-Rank Test. The results showed that 43.5% of participants experienced an increase in knowledge scores, 39.1% remained the same, and 17.4% decreased. The conclusion of this activity is that community-based psychoeducation has the potential to strengthen family preparedness, although further development of more comprehensive instruments and adaptation of learning methods to local contexts are needed.